Chemical composition and antioxidant activity of leaf essential oil from Calyptranthes concinna DC. (Myrtaceae) (Acta Scientiarum. Biological Sciences, 2022)
The biodiversity found in Brazilian’s ecosystems brings the possibility of discovering new natural products with wide application potentials. However, knowing their availability and chemical composition is crucial. Thus, the aim of this study was to evaluate the extraction yield, chemical composition and antioxidant activity of essential oil from fresh leaves of Calyptranthes concinna DC., a native species of Myrtaceae occurring in Brazilian Atlantic Rain Forest. Plant samples were collected in Southeastern Brazil and the essential oil was extracted by hydrodistillation. The chemical composition was evaluated by Gas Chromatography associated with Mass Spectrometry and antioxidant activity was measured using ABTS, DPPH and FRAP methods. The extraction yield obtained was 0.015% (v), and the chemical composition revealed elemicin, a phenylpropanoid as the major component (36.46%). Still, Î²-caryophyllene (16.94%), germacrene B (8.28%) and spathulenol (7.33%) proved to be relevant for the same essential oil. Antioxidant activity was obtained for ABTS and DPPH radical scavenge (134.82 ± 2,9 and 93.70 ± 1.7 µM TE mL-1, respectively) and FRAP (11.31 ± 0.2 µM FeSO4 mL-1 OE), revealing hydrogen-donation as the main antioxidant mechanism. To our knowledge, this is the first report of antioxidant activity of C. concinna essential oil. The product presented compounds of great relevance, with possibilities of application in different areas including food, agriculture and pharmaceutical segments